2021
DOI: 10.1007/s00107-020-01643-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic response of insulated steel angle brackets used for cross-laminated timber connections

Abstract: In cross-laminated timber (CLT) buildings, in order to reduce the disturbing transmission of sound over the flanking parts, special insulation layers are used between the CLT walls and slabs, together with insulated angle-bracket connections. However, the influence of such CLT connections and insulation layers on the seismic resistance of CLT structures has not yet been studied. In this paper, experimental investigation on CLT panels installed on insulation bedding and fastened to the CLT floor using an innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Numerous researchers have studied these lateral resisting elements. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Firstly, various handcrafted notch geometries of corner joints (e.g., Saddle, Norwegian, Daimon, and Dovetail notch) were proposed and their performance was investigated under in-plane lateral loads. [7][8][9] Then, the lateral load resistance of the standard half lapped, and dovetail corner joints of modern log houses were examined via experiments, [10,12,13] numerical methods, [12][13][14][15] and analytical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers have studied these lateral resisting elements. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Firstly, various handcrafted notch geometries of corner joints (e.g., Saddle, Norwegian, Daimon, and Dovetail notch) were proposed and their performance was investigated under in-plane lateral loads. [7][8][9] Then, the lateral load resistance of the standard half lapped, and dovetail corner joints of modern log houses were examined via experiments, [10,12,13] numerical methods, [12][13][14][15] and analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[16] In addition, the two main types of LF connections were investigated, including a sill log element on various floor types [7,17,18] and angle brackets. [10,11] In the case of log-log friction, the friction coefficients under various vertical loads and sliding characteristics between timber log layers were studied experimentally, [12,19] and it was found that the sliding characteristic between layers of log elements could not be included in the lateral load resistance prediction [10] because of its sensitivity to various parameters. Some previous works [9,[21][22][23] also focused on the improvement of the lateral load resistance between log layers using reinforcement material.…”
Section: Introductionmentioning
confidence: 99%
“…The first was a perfect elasto-plastic model (EPM) [13,21]. Although this method was originally proposed for analyzing wood-frame structures, there are many examples of researchers applying it to joint analyses [22][23][24][25]. The method for determining the yield load is illustrated in Fig.…”
Section: Yield Loadmentioning
confidence: 99%
“…Since the range of possible loading rates is wide, our recent experimental campaign with CLT panels also investigated the effect of loading rate on the response of panels. The aim of the campaign was to investigate the behaviour of CLT panels (2490/2490/100 mm 3-layer) connected to CLT slabs with special insulated angle-bracket connections that can withstand both shear and tensile forces [19], as well as the influence of different sound insulation layers under the panels on the response. More detailed information about the entire experimental campaign and the results can be found in [20].…”
Section: Influence Of the Loading Rate On The Behaviour Of Clt Shear ...mentioning
confidence: 99%